2004
DOI: 10.1007/bf03181532
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of submerged water jets by visualization method

Abstract: This paper is concerned with an experimental investigation on plane submerged water jets discharged into quiescent water in an open channel. Flows are visualized by using hydrogen bubbles, solid particles and dye. The results show that the jets attaching to the water surface by the Coanda effect are classified into six types according to their behavior after issuing from the nozzle, and that the self-induced vibration of the jet, which is one of six flow patterns, occurs under the condition of the reduced Frou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Similar diagrams with figures 12(a) and (b) were obtained in experiments by Sudo et al (1998), Shimada et al (2004) and Tsunoda et al (2006) although their experiments were performed at much larger Reynolds numbers such as Re = 4430-177 00 (Sudo et al 1998, Shimada et al 2004 and Re = 2500 (Tsunoda et al 2006) and the length of the channel (L in figure 1) was much longer. They concluded that the direction of deflection of the flow is determined solely by the values of h 1 and h 2 , independently of the Reynolds number, and they attributed the mechanism of deflection to the Coanda effect.…”
Section: Effect Of the Height Of The Inlet Throatsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar diagrams with figures 12(a) and (b) were obtained in experiments by Sudo et al (1998), Shimada et al (2004) and Tsunoda et al (2006) although their experiments were performed at much larger Reynolds numbers such as Re = 4430-177 00 (Sudo et al 1998, Shimada et al 2004 and Re = 2500 (Tsunoda et al 2006) and the length of the channel (L in figure 1) was much longer. They concluded that the direction of deflection of the flow is determined solely by the values of h 1 and h 2 , independently of the Reynolds number, and they attributed the mechanism of deflection to the Coanda effect.…”
Section: Effect Of the Height Of The Inlet Throatsupporting
confidence: 85%
“…It has been long thought that the deflection of jets issuing at a middle height is uniquely determined by the configuration of the reservoir. However, Sudo et al (1998) and Shimada et al (2004) found in their experiments that a planar submerged water jet discharged into a reservoir with a free surface deflects towards either of the two boundaries, which was confirmed by Tsunoda et al (2006). The two kinds of deflected flow are realized in a range of the depth and the height of the inlet throat or nozzle, while the flow always deflects either to the free surface or to the bottom in the two extreme conditions where the throat is close to the free surface or to the bottom, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Shimada et al [17] carried out an investigation on the flow pattern and self-induced vibration of relatively low-speed submerged water jets by dye visualization method. Hutli and Nedeljkovic [18] did an investigation on the frequency of cavitation cloud shedding in submerged cavitating jet by cloud shape analysis.…”
mentioning
confidence: 99%
“…Most of the researchers found that the jet-flipping or similar flow patterns occurred with relatively low submergence. Coates (1976), Johnston and Halliwell (1986) and Shimada et al(2004) observed that the jet regime can be a surface jet, a bed jet or an alternating bed-surface jet (jet-flipping) for experiments without an erodible sediment bed. Similarly, Lin et al (2008) observed the oscillating flow patterns in vertical drop pool structures.…”
Section: Effects Of Tailwater Depth and Velocity On Jet-flippingmentioning
confidence: 99%
“…Jet-flipping can induce an erroneous judgment of the equilibrium state and therefore inaccurate scour prediction. Coates (1976), Johnston and Halliwell (1986) and Shimada et al(2004) observed that the jet flow can be a surface jet, bed jet or bed-surface jet in their studies under no sediment transport conditions. For situations with a sediment bed, Johnston (1990) and Mazurek et al (2009) also noted these 3 types of jet behaviours.…”
Section: Introductionmentioning
confidence: 99%